Competition between isolates of Septoria tritici Rog. Ex Desm. in bread wheat (Triticum aestivum L.) - Leyva Mir, Santos Gerardo; Zavaleta Mejía, Emma; Gilchrists Saavedra, Lucy; Khairallah, Mireille; Mariscal Amaro, Luis Antonio (Revista Mexicana de Ciencias Agrícolas, 2018)
Inoculations with different isolates are done to obtain wheat genotypes resistant to Septoria tritici; however, there is evidence of competition between the isolates that overestimates the resistance response of the genotypes. To check this, the aim of this study was to test three wheat genotypes with different levels of resistance to this fungus, which was inoculated with isolates P8, P9 and B1, individually and in mixtures. The experiment was established in 2006 under a split plot design with three replicates. Pycnidia were collected from the flag leaf and the lower leaf to identify, using RFLPs, the isolates that established and prevailed in the different genotypes. When P8, P9 and B1 were inoculated individually, the original isolate was recovered; when they were inoculated in mixture, P9 was not re-isolated, which evidenced the competition between the isolates and the low aggressiveness of P9.B1 had the highest recovery rate. With B1 and P8, genetic variants were reisolated whose presence was inf luenced by the wheat genotype and the isolates with which they were mixed. Because competition can reduce the aggressiveness and pathogenicity of the isolates inoculated in mixture, the best strategy in wheat breeding programs to select resistance is to inoculate the isolates individually.
Keywords: aggressiveness; competition; genetic variants; pycnidia